Overcoming thermal quenching in X-ray scintillators through multi-excited state switching - Wang, Min (2024)
X-ray scintillators have gained significant attention in medical diagnostics and industrial applications. Despite their widespread utility, scintillator development faces a significant hurdle when exposed to elevated temperatures, as it usually results in reduced scintillation efficiency and diminished luminescence output. Here we report a molecular design strategy based on a hybrid perovskite (TpyBiCl5) that overcomes thermal quenching through multi-excited state switching. The structure of perovskite provides a platform to modulate the luminescence centers. The rigid framework constructed by this perovskite structure stabilized its triplet states, resulting in TpyBiCl5 exhibiting an approximately 12 times higher (45 % vs. 3.8 %) photoluminescence quantum yield of room temperature phosphorescence than that of its organic ligand (Tpy). Most importantly, the interactions between the components of this perovskite enable the mixing of different excited states, which has been revealed by experimental and theoretical investigations. The TpyBiCl5 scintillator exhibits a detection limit of 38.92 nGy s-1 at 213 K and a detection limit of 196.31 nGy s-1 at 353 K through scintillation mode switching between thermally activated delayed fluorescence and phosphorescence. This work opens up the possibility of solving the thermal quenching in X-ray scintillators by tuning different excited states.